Schizophrenia: A Review of the Syndrome. 1958
DOI: 10.1037/10604-001
|View full text |Cite
|
Sign up to set email alerts
|

The schizophrenic syndrome: A further elaboration of the unified theory of schizophrenia.

Abstract: Under certain circumstances, "construct" might be a technically preferable term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1962
1962
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…After analysis of these 33 cases, Darby concluded that autism should not be considered a disorder in itself, but an overt behavioral expression of a number of disorders. This concept is similar to the "final common pathway" concept introduced by Bellak (1958) with respect to adult schizophrenia. A later study of four autopsy cases (Williams, Hauser, Purpura, Delong, & Swisher, 1980) revealed no post mortem evidence of organic pathology.…”
Section: Neuropathological Studiesmentioning
confidence: 71%
“…After analysis of these 33 cases, Darby concluded that autism should not be considered a disorder in itself, but an overt behavioral expression of a number of disorders. This concept is similar to the "final common pathway" concept introduced by Bellak (1958) with respect to adult schizophrenia. A later study of four autopsy cases (Williams, Hauser, Purpura, Delong, & Swisher, 1980) revealed no post mortem evidence of organic pathology.…”
Section: Neuropathological Studiesmentioning
confidence: 71%
“…The selection of the 177 dichotomous items was not made on the basis of any elaborate theory of schizophrenia, but was guided by the view that the illness, irrespective of etiology, can be described as a disturbance of basic ego functions (including the autonomous ego functions) (cf. Bellak, 1958). The psychiatric questionnaires and the psychological tests, from which the items were taken, may Scand.…”
Section: Test Instrumentsmentioning
confidence: 99%
“…In recent years mterest m the early family environment of schizophremcs has shifted away from descnptive studies of parents and parent-child relationships to emphasis on family organization and mteraction pattems Conceptualization m this area of mvestigation has been particularly difficult, however, largely because of the complexity of the growmg breadth of empincal findmgs One concept that has found repeated utility m relatmg empincal findmgs to the larger body of developmental theory has been that of identification. Wahl (1956), for example, has suggested that schizophremcs experience environmental conditions which prevent adequate parental identification Bellak (1958) has stressed the need for good identification figures, addmg that if such figures are madequate the foimdation for the development of reahty testmg will be impaired Lidz and associates (eg,Lidz & Fleck,i960) have pointed out that self-identity comes to tiie child only through leammg interaction with parental models, and this process can proceed with reasonable smoothness only if these models can be followed and are able to transmit useful ways of living m society Recent studies of schizophrenia at Duke Umversity (Garmezy & Rodmck, 1959), demonstratmg relationships between premorbid adequacy and family organization, have suggested differential pattems of parental identification between good and poor premorbid schizophrenics Garmezy and Rodnick state that It would certainly be congruent with current knowledge of the identification process to find that the more assertive role of me father in good premorbid famihes is refiected m the greater social adequacy and maturity level achieved by their sons-an adequacy which is confirmed both by PhiUips Scale ratmgs based upon premorbid adjustment and labioratory performance imder stress dunng the psychosis (p 404)…”
mentioning
confidence: 99%